Enhancing Health Cadres' Competence in Identifying Community Health Problems Through the BagahTP.com Website in Cot Mancang, Aceh Besar - Iskandar, Iskandar; Yullyzar, Yullyzar; Ardiansyah, Muhammad; Nafila, Maisya; Tauhida, Sarah; Haliza, Alfa (Universitas Pahlawan Tuanku Tambusai, 2025)
Limited healthcare personnel and low adoption of digital technology in rural areas have resulted in manual screening and health data recording processes. This condition affects the early detection of chronic and infectious diseases and reduces the accuracy of Posyandu data. This Community Service Program aimed to enhance the competence of health cadres in Cot Mancang Village, Aceh Besar District, through three main trainings is health cadre competency improvement, digital-based health services, and strengthening health education capacity. Evaluation was conducted using pre-test and post-test on six main variables: application understanding, chronic diseases, infectious diseases, cadre roles, digital data, and follow-up actions. Results showed an average score improvement of 6.2%, from 0.77 to 0.84, with the highest increase in the infectious disease variable (0.50 to 0.88). These findings demonstrate that BagahTP.com effectively supports cadres in screening, early detection, and accurate health data recording at the Posyandu level.